2014
DOI: 10.1093/infdis/jiu297
|View full text |Cite
|
Sign up to set email alerts
|

HIV Type 1 (HIV-1) Proviral Reservoirs Decay Continuously Under Sustained Virologic Control in HIV-1–Infected Children Who Received Early Treatment

Abstract: Initiation of early effective cART during infancy significantly limits circulating levels of proviral and replication-competent HIV-1 and promotes continuous decay of viral reservoirs. Continued cART with reduction in HIV-1 reservoirs over time may facilitate HIV-1 eradication strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
100
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(117 citation statements)
references
References 32 publications
16
100
0
1
Order By: Relevance
“…In the case of the Mississippi baby and the Visconti cohort, cART was used to initiate treatment very early (before seroconversion), which is thought to have reduced the seeding of viral reservoirs, whilst preserving anti-HIV-1 immune function. This observation has been repeated in several other studies and highlights the potential benefits of early cART treatment to HIV-1 cure efforts [17-20]. Nevertheless, each of these cases has provided new information and strengthened the belief that a HIV-1 cure is indeed feasible.…”
Section: Hiv-1 Curementioning
confidence: 64%
“…In the case of the Mississippi baby and the Visconti cohort, cART was used to initiate treatment very early (before seroconversion), which is thought to have reduced the seeding of viral reservoirs, whilst preserving anti-HIV-1 immune function. This observation has been repeated in several other studies and highlights the potential benefits of early cART treatment to HIV-1 cure efforts [17-20]. Nevertheless, each of these cases has provided new information and strengthened the belief that a HIV-1 cure is indeed feasible.…”
Section: Hiv-1 Curementioning
confidence: 64%
“…This difference is linked to the duration of uncontrolled viral replication between initial infection and effective treatment. The lower level of HIV DNA in children treated early versus late correlates with a lower level of replication-competent virus (75).…”
Section: Time From Hiv-1 Infection To Treatment Initiation Influencesmentioning
confidence: 97%
“…More recently, an assay that dispenses with the extraction step has been proposed (70). Recent technical progress has permitted the development of HIV DNA quantification by digital droplet PCR (ddPCR), which does not require an external quantification standard (71)(72)(73)(74)(75)(76)(77). However, some false-positive signals have been observed with ddPCR, which can be a problem when this method is used for diagnosis (76).…”
Section: Dna Load In Resting Cd4mentioning
confidence: 99%
“…Some clinical studies have shown that early ART not only inhibits HIV-1 replication but also limits the size of viral reservoirs. Continued ART with a reduction in HIV-1 reservoirs over time may facilitate HIV-1 eradication strategies Jain et al 2013;Li and Gandhi 2014;Luzuriaga et al 2014).…”
Section: Current Potential Hiv Cure Strategiesmentioning
confidence: 99%